The revival of International Radio: Multinationals, religious broadcasters, foreign radio and Internet - Checa Godoy, Antonio (2013)
Without the uproar caused by the process regarding television, the Radio media has also been attracting, in recent decades, companies from different countries that have forged multinational empires, especially in the field of music Radio. This new supranational dimension of the Radio is also increased by the renewed rise of religious radio stations and new approaches to old propagandist radio, all also taking advantage of the possibilities offered by internet. Radio is now more international than ever.